Gaya Kepemimpinan Kepala Sekolah dalam Peningkatan Profesionalisme Guru PAI pada SD Negeri 2 Kota Subulussalam - Aswin Aswin; Saifullah Idris; Yusra Jamali (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2023)
The purpose of this research is to find out the following things: 1). Principal's leadership style in improving teacher discipline in SD Negeri 2 Kota Subulussalam, 2). Principal's leadership style in improving teacher performance in SD Negeri 2 Kota Subulussalam, 3). Principal's leadership style in improving teacher careers in SD Negeri 2 Kota Subulussalam, 4). To analyze the obstacles faced and the principal's solutions in applying the leadership style at SD Negeri 2 Kota Subulussalam. This study used a qualitative descriptive research method with data collection techniques through interviews, observation and documents. Data analysis techniques use: data reduction, data display, and conclusions or verification. The research location is at SDN 2 Subulussalam, Subulussalam City. The findings of this study are as follows: 1). In an effort to increase the Discipline of PAI teachers at the SDN 2 Subulussalam school, the Principal sets a good example for other teachers in terms of time discipline and rules at school, as well as supervising and controlling each teacher. 2). In improving the performance of PAI teachers at SDN 2 Subulussalam, Subulussalam City, the school principal provides support and motivation to teachers in carrying out their duties and responsibilities. The school principal also supervises, assesses and evaluates teacher performance and provides rewards for achieving teacher performance. 3). Among the programs and things that the Principal does to improve the career and performance of teachers is to provide opportunities for PAI teachers to receive coaching and attend training related to their respective fields, and provide other opportunities in a transparent manner, the principal also supports teachers who continue their Masters and Doctoral studies. 4). Obstacles faced by school principals in implementing leadership styles at SD Negeri 2 Kota Subulussalam include: Some teachers are still lacking time discipline, some teachers are late to school because of damaged infrastructure, do not use teaching tools, violate school rules, are not motivated to improve their performance, do not respond to exemplary from the principal, the lack of school infrastructure. Solutions made by the school principal in overcoming obstacles in increasing teacher professionalism at SDN 2 Subulussalam Subulussalam City include providing encouragement/motivation to teachers through self-help schools, implementing Fingerprint attendance in increasing time discipline for teachers, continuing teacher education through study permits. In addition to submitting requests for assistance to the government in overcoming the shortage of teachers, especially teachers in the field of study by hiring honorary teachers and a shortage of school infrastructure